Development of a trilipid-based liposome system as a delivery vector for plasmid dna in an mcf-7 cell line - Tseu, Gloria Yi Wei (2023)
Breast cancer has recorded an increase in incidence and mortality rates, especially among female patients, for the past decade globally. Currently, available treatments affect patients both physically and mentally initiating a safer alternative treatment and one of them is gene therapy. Clinical trials mostly utilise viruses to deliver genes but adverse immunological issues, which lead to multiple organ failure and even death are reported as side effects. Thus, non-viral vectors such as liposome, an alternative delivery system without immunological issues, are greatly considered. Liposomes, consisting of lipid bilayers made into nanoparticles as a form of the delivery system encompass a therapeutic gene cargo to protect and efficiently traverse through the biological barriers for effective gene delivery. This project aims to compare different formulation techniques to optimize the formulated liposome's physical characteristics. The optimum method was developed for formulating liposomes involving a combination of several methods and techniques. Liposome formulations involving DPPC, octadecylamine and cholesterol lipids at different ratios were looked into and found the best combination DPPC:octadecylamine:cholesterol at 18:72:10 ratio formed spherical agglomeration according to TEM imaging. The particle size of the non-viral vector produced was ~400nm with a positive zeta potential of ~60mV. The ability of the liposome formulation to encapsulate nucleic acid with different plasmid and liposome ratios was determined to be best at 1:7 ratio. The cytotoxicity of the liposome and nucleic acid complexes was determined using MTT cytotoxicity assay with ~65% cell viability at 2μg/μl showing lower toxicity compared to different formulations published in literature which used 5- 10 times lower concentration of dosage. Through this research, a formulation of liposome consisting of DPPC:octadecylamine: cholesterol at 18:72:10 ratio with a reporter gene (pcDNA3.1(+)eGFP) was developed and has shown promising size properties, zeta potential, encapsulation efficiency with low cytotoxicity as a potential non-viral gene therapy carrier for the treatment of breast cancer. The development of this liposome formulation is not limited to being used as a gene carrier for gene therapy specifically for breast cancer but has the potential as a targeted carrier for drugs, plant extracts and even proteins which can greatly benefit the advancement of forms of treatments for various diseases due to its limitless modification of the liposome as a nonviral vector.